2003
DOI: 10.1074/jbc.m213087200
|View full text |Cite
|
Sign up to set email alerts
|

Porin OmpP2 of Haemophilus influenzae Shows Specificity for Nicotinamide-derived Nucleotide Substrates

Abstract: Haemophilus influenzae has an absolute requirement for NAD (factor V) because it lacks all biosynthetic enzymes necessary for de novo synthesis of that cofactor. Therefore, growth in vitro requires the presence of NAD itself, NMN, or nicotinamide riboside (NR). To address uptake abilities of these compounds, we investigated outer membrane proteins. By analyzing ompP2 knockout mutants, we found that NAD and NMN uptake was prevented, whereas NR uptake was not. Through investigation of the properties of purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…The OM permeability to cephaloridine, when calculated from the data given (150), seems to be around 1 to 2 m s Ϫ1 , that is, similar to what was found in E. coli (462). Recently this porin was found to bind specifically NAD ϩ and nicotinamide mononucleotide with the half-saturation constant of 4 to 8 mM, apparently an adaptation to the growth requirement of this organism for nicotinamide nucleotides (17). This again seems to be an example showing that the distinction between the general, nonspecific porins and specific channels is far from absolute.…”
Section: Other Porinsmentioning
confidence: 99%
“…The OM permeability to cephaloridine, when calculated from the data given (150), seems to be around 1 to 2 m s Ϫ1 , that is, similar to what was found in E. coli (462). Recently this porin was found to bind specifically NAD ϩ and nicotinamide mononucleotide with the half-saturation constant of 4 to 8 mM, apparently an adaptation to the growth requirement of this organism for nicotinamide nucleotides (17). This again seems to be an example showing that the distinction between the general, nonspecific porins and specific channels is far from absolute.…”
Section: Other Porinsmentioning
confidence: 99%
“…Liquid cultures of N. meningitidis were grown in Mueller-Hinton broth supplemented with Vitox at 37°C with agitation. The ΔompP2 mutant of H. influenzae Rd was a gift from Joachim Reidl, Biozentrum der Universität Würzburg, Am Hubland, Germany (29).…”
Section: Methodsmentioning
confidence: 99%
“…We characterized two enzymes, a nucleotide phosphatase encoded by the e(P4) outer membrane protein and NadN, an NAD ؉ nucleotidase located in the periplasm (23,40,44). In addition, we showed that NAD ؉ and NMN cross the outer membrane mainly via the OmpP2 porin (2). However, only NR can be utilized by the transport system located in the inner membrane (19,42), which is encoded by a homologue of pnuC.…”
mentioning
confidence: 99%